Quality assessment of cellular therapies: the emerging role of molecular assays - Stroncek, David F. (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2010)
Cellular therapies are becoming increasingly important in treating cancer, hematologic malignancies, autoimmune disorders, and damaged tissue. These therapies are becoming more effective and are being used more frequently, but they are also becoming more complex. As a result, quality testing is becoming an increasingly important part of cellular therapy. Cellular therapies should be tested at several points during their production. The starting material, intermediate products and the final product are usually analyzed. Products are evaluated at critical steps in the manufacturing process and at the end of production prior to the release of the product for clinical use. In addition, the donor of the starting biologic material is usually evaluated. The testing of cellular therapies for stability, consistency, comparability and potency is especially challenging. We and others have found that global gene and microRNA expression analysis is useful for comparability testing and will likely be useful for potency, stability and consistency testing. Several examples of the use of gene expression analysis for assessing cellular therapies are presented.